Halal Branding; A Religious Doctrine in the Development of Islamic Da'wah - Abdul Rachman (Journal of Digital Marketing and Halal Industry, 2020)
Halal Branding has become a trend and will continue to grow. Halal Branding is implemented in almost all fields, especially food, medicine, cosmetics, fashion, and even tourism. Muslims use halal Branding as a guarantee of consuming a product to avoid sins. Meanwhile, Halal Branding is used by non-Muslims, one of which is for business and consumption purposes. Halal Branding not only guarantees the product is healthy and safe but also as Islamic religious doctrine. This study aims to determine how much Halal Branding is trying to ground the halal concept as the best concept in the halal lifestyle. Another objective is to observe various approaches in developing Halal Branding so that the existence of Halal Branding as a religious doctrine can become a medium for preaching to all groups, including non-Muslims, so that the acceleration of the development of Islamic da'wah will be more aggressive. This paper is expected to be used as knowledge and development of halal in life aspects to be appropriately implemented. Research results show that halal Branding indirectly into religious doctrine on halal products and become a useful tool of Islamic da'wah.